2)Упростите выражение 9x^3y^-2 * 3^-1x^-2y^3

0 голосов
22 просмотров

2)Упростите выражение 9x^3y^-2 * 3^-1x^-2y^3


Алгебра (105 баллов) | 22 просмотров
Дан 1 ответ
0 голосов
Правильный ответ
9x^3y^{-2}3^{-1}x^{-2}y^3=
используем свойство степени с отрицательным показателем
A^{-n}=\frac{1}{A^n}

перепишем
=\frac{9x^3y^3}{3^1y^2x^2}=
сокращаем 
3xy

либо так:
используем свойство A^1=A
A^n:A^m=\frac{A^n}{A^m}=A^{n-m}[/tex]

\frac{9}{3}*x^{3-2}y^{3-2}=3xy
ответ: 3xy
============
либо так 
9x^3y^{-2}3^{-1}x^{-2}y^3=
3^2x^3y^{-2}3^{-1}x^{-2}y^3=
используем свойства
A^n*a^m=A^{n+m}
A^1=A

получим
3^{2+(-1)}x^{3+(-2)}y^{(-2)+3}=3^1x^1y^1=3xy
image
(407k баллов)